La poesia è una telegrafia (ENTHYMEMA, 2019)
We mostly think of the free act, the creative gesture, as something endometabolic, adhering to a deep and introverted disposition, like an action that responds to the will of the agent, sincere, faithful. The phantom forces us to turn, to a change of perspective. It is written down there, away from our body, in a separate space, thanks to a telegraphy. If it leaps out of secret crypts, the latter are not intimate, assimilated places, but mundane spaces that share with the crypt the latency, the unconscious character, not the proximity to the subject. The phantom comes from afar and we give it form not by shaping materials between the hands, but through distant tactility. Hands-free.
Keywords: Lacan; poetry; creative act; telegraphy; phantom